Al-Tarbiyah Al-Ijtimaiyyah Dalam Perspektif Al-Qur’an Dan Hadits - Hastutie, Ghina (AL MURABBI, 2024)
Social education is the essence inherent in an educational activity where education is carried out in order to help the process of social development so that students will choose and implement good social manners so that they can live in harmony among their community. This paper aims to analyze the purpose of social education from the perspective of the Al-Qur'an and Hadith and the phases of child development in social education. Apart from that, this research also aims to find out the meaning of social education in the perspective of the Al-Qur'an and Hadith and to find out the meaning of the phases of children's development in social education. This research is library research uses qualitative methods with a text analysis approach to the Al-Qur'an and Hadith. Text analysis will involve in-depth study of the verses of the Qur'an and Hadith relating to education. Apart from that, this research will also involve an in-depth literature study on social education from the perspective of the Al-Qur’an and Hadith. The results of this research show that the values ​​of social education are: gentleness which is related to efforts to become a person who can respect other people, be caring and tolerant; Forgiveness or forgiving is a trait that contains high values ​​of humanity and sacrifice in social education which is closely related to humanitarian considerations and deliberation is the development of attitudes that a person guides in society to make himself have a living existence in society.